Examining The EFL Students Motivation at The Vocational High School of Tourism During The Process of Online English Learning - Turini Erawati; Wendi Kusriandi; Setia Budiyanti; Putri Ghina Salamah (Syntax Corporation, 2022)
Learning motivation can determine the result of students' online learning by several factors, namely internal and external factors (from within students) and external factors (from outside students). The purpose of this study is to determine the internal and external factors that affect students' learning motivation in class XI AKP 2 SMK Pariwisata Kota Cirebon in online learning. This qualitative descriptive research collects the data from questionnaires and unstructured observations interviews. The questionnaire used in this study was 21 questions; unstructured observation and unstructured interviews. The results obtained from the questionnaire show that the internal factors that can affect students' learning motivation in online learning consist of four indicators, namely Interests, Needs, Attitudes, and Intelligence, with percentage values ​​of 74.6%, 55.6%, 79.5%, and 77.8%. External factors that influence students' learning motivation in online learning consist of three indicators: the Family Environment, School Environment, and Community Environments, with the percentage values ​​of 80.2%, 62.5%, and 75.7%.